Gender Differences in Ethical Perceptions of Salespeople: An Empirical Examination in Turkey - Ergeneli, Azize (Journal of business ethics, 2002)
Researchers on gender and ethical decision-making have recently emphasized the differences between men's and women's ethical perceptions. This study is concerned with the perceptions of salespeople working in clothing and medical equipment sectors in Turkey. It regards the perceptions of colleagues of opposing genders in ethically questionable situations. The evaluation of salespeople's responses for 14 ethical scenarios indicates that there is no significant difference in ethical perception based on gender. Each gender predicted that their counterpart's response would be the same as their own. The study also examined the effects of some demographic factors as well as the firm's sector on the salespeople's ethical perceptions and found that there are both differences and similarities in detail between genders of salespeople within ethically questionable situations.